Believe It or Not – No Support for an Effect of Providing Explanatory or Threat-Related Information on Conspiracy Theories' Credibility. Issue 1 (19th October 2021) - Meuer, Marcel; Oeberst, Aileen; Imhoff, Roland
Past research suggests that certain content features of conspiracy theories may foster their credibility. In two experimental studies ( N = 293), we examined whether conspiracy theories that explicitly offer a broad explanation for the respective phenomena and/or identify a potential threat posed by conspirators are granted more credibility than conspiracy theories lacking such information. Furthermore, we tested whether people with a pronounced predisposition to believe in conspiracies are particularly susceptible to such information. To this end, participants judged the credibility of four conspiracy theories that varied in the provision of explanatory and threat-related information. Interestingly, the specific type of information provided was not decisive. Instead, credibility judgments were only driven by people's predisposition to believe in conspiracies. Findings suggest that there is no mechanistic, almost automatic effect of merely adding specific information and highlight the relevance of people's conspiratorial mindset for the evaluation of conspiracy theories.